The Influence Of Competence, Integrity And Organizational Culture On Employee Performance In Job Satisfaction Moderation At Bank Indonesia Provincial Representative Offices North Sumatra - Muhammad Zailani Sinaga; Mesra B (International Journal of Management, Economic and Accounting, 2024)
Today, a company's ability to successfully navigate a highly competitive landscape of advantage depends solely on its ability to organize and manage its human resources effectively. Working with clear organizational goals and strategies will result in human resource performance. So, performance is about what is done and how the work is done, as well as how the work is completed and the results obtained from it. The results of this study are as follows; Organizational Culture had a positive and insignificant effect on Employee Performance with the original sample of 0.054 and p values of 0.293. Organizational Culture had a positive and significant effect on Work Motivation with the original sample value of 0.606 and p values of 0.000. Organizational Climate has a positive and significant effect on Employee Performance with an original sample value of 0.137 and pvalues of 0.039. Organizational Climate had a positive and significant effect on Work Motivation with the original ampel value of 0.222 and p values of 0.003. Work Motivation had a positive and significant effect on Employee Performance with the original sample value of 0.779 and p values of 0.000. Organizational Culture has a positive and significant effect on employee performance through indirect Work Motivation with the original sample value of 0.472 and p values of 0.000. Organizational Climate has a positive and significant effect on employee performance through indirect Work Motivation with the original sample value of 0.173 and p values of 0.003.